Virtual Reality as a Technological-Aided Solution to Support Communication in Persons With Neurodegenerative Diseases and Acquired Brain Injury During COVID-19 Pandemic - Stasolla, Fabrizio; Matamala-Gomez, Marta; Bernini, Sara; Caffò, Alessandro O.; Bottiroli, Sara (Frontiers in Public Health, 2021)
The COVID-19 pandemic situation dramatically impacted our lives and pose serious challenges to public health and medical delivery services. For monitoring viral diffusion, social distancing has been adopted as a preventive measure all over the world with a substantial interruption of the medical assistance for many individuals with neurological disorders. Besides the daily passivity, isolation, and withdrawal, patients with neurodegenerative diseases may experience communication difficulties without independently access leisure opportunities and communication with their relatives as a negative outcome. An increased burden of the caregivers may be observed accordingly. To tackle such communication issues, assistive-technology-based strategies may be envisaged for facilitating communication with distant partners. This manuscript proposes a new assistive-technology-based approach in using virtual reality and virtual body ownership illusions to enable patients with neurological diseases and severe to profound disabilities communication with their relatives in case of isolation of the patient inside the hospital during the COVID-19 pandemic situation. We hypothesized that the proposed intervention may improve the patients’ social interactions enhancing their quality of life and mental well-being, avoiding isolation and negative psychological and cognitive effects.